CAPITAL STRUCTURE AND FIRM VALUE : A CROSS-COUNTRY ANALYSIS OF INDUSTRIAL COMPANIES - Monica, Ordelia Elizabeth; Risty, Ilyona (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Capital structure and firm value are the variables tested in this study by analyzing cross-country samples from Indonesia, China, and Thailand. This study uses data from the S&P Capital IQ database for 2022, consisting of companies from various industrial sectors. This study uses STATA software for data processing and regression analysis to test the effect between the two variables. The results of the study that have been empirically tested find a positive relationship between capital structure and firm value of companies in all three countries. In China, Indonesia, and Thailand, where corporate governance structures and ownership patterns are different, the impact of debt can vary. In markets with weaker governance, higher leverage can be beneficial to limit managerial opportunism. However, excessive debt can lead to financial distress, increasing the likelihood of value destruction rather than value enhancement. Therefore, companies must balance debt financing to minimize agency costs while maximizing firm value. This study contributes to stakeholders, investors, and policymakers in making strategic financing decisions. Further research is recommended to explore firm-specific and macroeconomic factors that are closely related to capital and firm value in different economic conditions.